Analysis of Hydro Motor Velocity Stabilization - Lapinskas, A.; Kirka, A.; Lapinskas, R. (Elektronika ir Elektrotechnika, 2008)
Various means such as throttles, flow regulators, variable displacement hydraulic machines, etc. are used for the flow regulation and control in the complex hydraulic systems. One of the functions, which often fall on a hydraulic drive, is speed stabilization of operating parts at a variable load. For this purpose flow regulators or hydraulic drives with variable displacement pumps and hydraulic motors may be used. This study deals with a task concerning the regulatory control of the hydraulic motor speed by using a positive displacement flow divider with variable displacement sections. Two different ways used for the connection of the flow divider into the hydraulic system and the possible methods for the control of the variable displacement of its sections have been considered and the control algorithms and operating factors have been developed. Ill. 6, bibl. 5 (in Lithuanian; summaries in English, Russian, Lithuanian).